Trade and Innovation in the Korean Information and Communication Technology Sector Trade and Innovation Project - Case Study No. 5 - Onodera, Osamu (OECD Trade Policy Papers, 2008)
This paper is one of five case studies which is a part of a larger project looking at the various effects that trade and investment can have on innovation. This paper studies the effect of trade and investment liberalisation on Korea's Information and communication technology (ICT) sector and finds that trade and investment have played a crucial role in innovation in the sector. In the initial stages of development, imported capital goods and components, joint ventures, licensing and Original Equipment Manufacturer (OEM) contracts were important sources of technology and exports were key to gain the necessary economies of scale for innovation. Free trade and investment policies in the 1990s and stronger protection of intellectual property rights have led to an increase in R&D and innovation and has led to the transformation of Korea into a knowledge based economy in the recent decade